Real-life effectiveness of once-daily single-inhaler triple therapy (FF-UMEC-VI) after switching from dual therapy (ICS-LABA) in patients with symptomatic asthma: trelegy ellipta for real asthma control study - Kushima, Yoshitomo; Shimizu, Yasuo; Arai, Ryo; Chibana, Kazuyuki; Shimizu, Yuka; Amagai, Masahiro; Takemasa, Akihiro; Ikeda, Naoya; Masawa, Meitetsu; Kushima, Atsushi; Okutomi, Hiroaki; Nakamura, Yusuke; et al. (Frontiers in Allergy, 2025)
IntroductionA well-designed, protocol-driven randomized controlled trial (RCT) has demonstrated the efficacy of fluticasone furoate-umeclidinium-vilanterol (FF-UMEC-VI) in patients with asthma, but there is a lack of real-world data that can be used to translate the results of the RCT into clinical practice. This study evaluated the efficacy of switching the therapy from inhaled corticosteroid-long-acting β2-agonists (ICS-LABAs) to FF-UMEC-VI at the equivalent corticosteroid dose in a real-world setting.MethodsA prospective, three-month, open-label, parallel-group, switching therapy trial was performed in patients with symptomatic asthma under routine management. Patients receiving low-to-medium doses of ICS-LABAs were switched to FF-UMEC-VI (100–62.5–25 µg, once daily) (T100 group), and patients receiving a high dose of ICS-LABAs were switched to FF-UMEC-VI (200–62.5–25 µg, once daily) (T200 group). The primary outcome was the change from baseline in forced expiratory volume in 1 s (ΔFEV1) at week 12, and the secondary outcomes were the improvement in fractional exhaled nitric oxide (FeNO), the asthma symptoms evaluated using the asthma control test (ACT), and the cough severity evaluated using the visual analog scale (VAS).ResultsThirty-five patients were switched to T100, and thirty patients were switched to T200. The ΔFEV1 was improved by more than 100 ml at 8 weeks after switching in both groups (T100, 110.4 ± 39.8 ml; T200, 117.1 ± 39.8 ml) (p < 0.05) but slightly decreased at 12 weeks. ACT also improved by more than 3 points at 8 weeks after switching and was maintained to 12 weeks in both groups (p < 0.05). Patients with ACT scores of <20 (i.e., poor control) before switching showed a greater improvement in the symptoms during T100 therapy, and 92% had reached an ACT score of >20 (i.e., good control). FeNO in the T100 group was decreased at 4 weeks (p < 0.05). Cough VAS also significantly decreased but did not reach a minimal clinically important difference.ConclusionsIn patients with symptomatic asthma showing insufficient control, an improvement in the asthma symptoms was observed after switching to FF-UMEC-VI at the equivalent corticosteroid dose, accompanied by an improvement in FEV1.